Intraocular lens calculation formula selection for short eyes: based on axial length and anterior chamber depth - Ruoxi Gao; Jiaqing Zhang; Xiaotong Han; Yiguo Huang; Ruoxuan Huang; Jinfeng Ye; Ling Wen; Xiaozhang Qiu; Xiaoyun Chen; Xuhua Tan; Lixia Luo (BMC Ophthalmology)
Abstract Purpose To evaluate the predictive accuracy of 11 intraocular lens (IOL) calculation formulas in eyes with an axial length (AL) less than 22.00 mm. Methods New-generation formulas (Barrett Universal II [BUII], Emmetropia Verifying Optical [EVO] 2.0, Hill-Radial Basis Function [Hill-RBF] 3.0, Hoffer QST, K6, Kane, Pearl-DGS) and traditional formulas (Haigis, Hoffer Q, Holladay 1 and SRK/T) were evaluated for predictive accuracy. Subgroup analyses were performed based on AL and anterior chamber depth (ACD). Results The study enrolled a total of 184 eyes from 184 patients. The BUII, Hoffer QST, Hoffer Q, Holladay 1, and SRK/T showed myopic shifts (-0.49 to -0.18 diopters [D], P < 0.05), whereas K6 displayed a hyperopic shift (0.11 D, P = 0.03). The Kane exhibited no systematic bias (-0.07 D), and yielded lower mean absolute error (MAE) (0.48 D, P < 0.05) and root mean square absolute error (RMSAE) (0.65 D, P < 0.01). For eyes with an AL ≤ 21.5 mm and an ACD > 2.5 mm, the Pearl-DGS displayed the smallest MAE (0.43 D) and lowest RMSAE (0.57 D), while other new-generation formulas showed relatively worse performance (MAE: 0.46 to 0.67 D; RMSAE: 0.60 to 0.84 D). Conclusion The Kane formula showed the highest accuracy in short eyes, whereas the Pearl-DGS had superior performance in eyes with a relatively shorter AL and deeper ACD. Clinical trial number Not applicable.